A Mathematical Model for Solid Population Balance in a 7.5MW FBC Power Plant using Cotton Stalk - Singh, Karamdeep (My University, 2008)
The arrival time of a space probe traveling to Saturn can be predicted more accurately than the behavior of a fluidized bed chemical reactor. Either a gas or a liquid can fluidize a bed of particles. In this thesis, the focus is purely on gas-solid fluidization. Taking data from a 7.5 MW FBC power plant, a mathematical model has been developed for solid population balance. The initial part of the development included calculation of physico-chemical parameters, developing a model that fits in the size distribution data and then further extending this model to calculate the carryover probability density and bed charcoal weight.
M.E. (CAD/CAM and Robotics)
Keywords: Fluidization; minimum fluidization velocity; solid population balance